Giant days. Volume thirteen - Allison, John, 1976-; Allison, John, 1976- (BOOM! Box, 2020)
"Everything's going fine for Esther - she’s only dealing with a past break up, facing her own mortality and the pressure of an essay contest that could change her life. Don’t worry, she’s got everything figured out... except for the getting everything figured out part. Otherwise she’s not racing towards imminent disaster. But for McGraw, the tough realities of life hit hard as he learns about the loss of someone close to him and has to find a way to process this shocking news."--Provided by publisher.